2020
DOI: 10.1115/1.4046036
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Micro-Electrochemical Machining Process for V-Shaped Grooves

Abstract: Microstructures determine flow properties of microfluidic chip. Micromold forming is an effective method to realize mass manufacturing of microfluidic chips. This requires to machine some kind of special microstructure of high surface quality on a metal/alloy workpiece. Micro V-shaped grooves are the typical microstructures of the chip micromolds used for controlling microfluid or weld packaging. In this research, a scanning micro-electrochemical machining (ECM) process of V-shaped grooves is proposed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was found that taper tool tip enhances the through-hole drilling and penetration. Zhong et al 21 fabricated a tungsten micro-tool with a taper angle of 30 degrees using micro-EDM. With the help of a fabricated tool, a V-shaped groove of 125 µm depth was fabricated with the help of EMM.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that taper tool tip enhances the through-hole drilling and penetration. Zhong et al 21 fabricated a tungsten micro-tool with a taper angle of 30 degrees using micro-EDM. With the help of a fabricated tool, a V-shaped groove of 125 µm depth was fabricated with the help of EMM.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments show that the device meets the design requirements. ECM machine tools are developing towards large-scale, intelligent and high-precision [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%